The Afixation in Karo Language - Sembiring, Gunawan; Mentari, Suci; Effendi, Sultan Salman (TALENTA Publisher, 2023)
This study aims to reveal the process of affixation and potential forms in the Karo language at the Pancur Batu Traditional Market. The theory used in this paper is the theory proposed by experts in the field of morphology. The approach used is a generative morphological theory [1][2]. The basic units of the lexicon are